Integration of Technology and Social Media in Islamic Religious Education Learning in the Digital Era - Fikratul Munawarah; Acisnawati Acisnawati; Hasmudin Agus; Budiman Budiman; Muhammad Tang; Juhasdi Susono (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The development of information technology and social media has brought significant changes to educational practices, including in the learning of Islamic Religious Education (PAI). This condition demands the integration of technology that is not only oriented toward ease of access but also toward strengthening the values and goals of Islamic education. The integration of technology and social media in Islamic Religious Education (PAI) learning becomes relevant to improve the quality of the learning process, expand learning resources, and encourage active participation of students in the digital era. However, the use of technology in religious education also presents challenges that need to be addressed to ensure they do not contradict Islamic values. Based on that context, this research aims to analyze the integration of technology and social media in Islamic Religious Education and identify the accompanying opportunities and challenges. This research uses a literature study method by reviewing various scientific sources related to educational technology, social media, digital literacy, and Islamic Religious Education (PAI) learning. The study results show that the integration of technology and social media can enhance students' learning motivation, activity, and understanding thru the use of digital platforms and online learning media. However, challenges such as the digital divide, low digital literacy, and the potential for media misuse still require attention. Therefore, the integration of technology in PAI learning needs to be accompanied by strengthening digital literacy, ethical guidance, and supervision based on Islamic values so that educational goals can be optimally achieved